1989
DOI: 10.1152/ajpendo.1989.256.4.e494
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged increase in insulin-stimulated glucose transport in muscle after exercise

Abstract: Exercise can induce short-term increases in the sensitivity and responsiveness of skeletal muscle glucose transport to insulin. The purpose of this study was to determine the effect of carbohydrate deprivation on the persistence of increased insulin sensitivity and responsiveness after a bout of exercise. Three hours after a bout of exercise, epitrochlearis muscles from carbohydrate-deprived (fat fed) rats showed a 25% greater increase in 3-O-methylglucose (3-MG) transport in response to a maximal insulin stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
277
0
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(292 citation statements)
references
References 17 publications
11
277
0
4
Order By: Relevance
“…This is consistent with previous reports of increased whole body or skeletal muscle insulin sensitivity persisting for 4 -48 h after a single bout of exercise in humans (34,46,54) and 4 -48 h after acute exercise in rodents (8,18,44). This is the first report of exercise-induced increases in insulin sensitivity in a nonhuman large animal.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is consistent with previous reports of increased whole body or skeletal muscle insulin sensitivity persisting for 4 -48 h after a single bout of exercise in humans (34,46,54) and 4 -48 h after acute exercise in rodents (8,18,44). This is the first report of exercise-induced increases in insulin sensitivity in a nonhuman large animal.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies in humans and rodents have reported increased insulin sensitivity after either higher-intensity or longer-duration acute exercise protocols than used in the present study (3,8,15,19,23,34,43,44,54). The exercise intensity achieved in the present study by sheep in the intensive exercise test (30 min, 8% slope, 4 -4.4 km/h) is probably ϳ50 -60% of V O 2max , based on studies in pregnant sheep (26).…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…40,41 The smaller effect of exercise on postprandial insulin concentrations when energy was replaced, compared to exercise with an energy deficit, is likely due to increased post-exercise repletion of muscle glycogen stores following the additional food that was provided in this trial, as restricting carbohydrate intake following exercise prolongs the duration of enhanced insulin sensitivity. 42 Our findings are consistent with long-term exercise training studies which indicate that exercise training without weight or fat loss (suggesting the absence of an exercise-induced energy deficit) improves insulin sensitivity, but that exercise with weight loss induces larger changes. 43 Thus, it seems clear that the insulinsensitizing effects of exercise are maximized when the energy expended is not replaced by increasing energy intake, however, the extent to which a residual benefit occurs when the energy expended is replaced is unclear.…”
Section: Exercise and Postprandial Metabolism Fl Burton Et Alsupporting
confidence: 90%
“…The insulinindependent effect is evident during and shortly after exercise, but it reverses relatively rapidly, with most of the effect typically lost ϳ3-4 h postexercise in rat muscle (10,43). As the exercise effect on insulin-independent glucose transport subsides, glucose transport in the presence of a physiological insulin concentration can be substantially elevated (9,10,32,43).…”
mentioning
confidence: 99%